Lessons Learned from the Implementation of xGTWay families of Unit Testing Tool - Kamal Z., Zamli; ‘Afaf Abdul Karim, Maryam; Rozmie Razif, Othman (2012)
Unit testing can be a long and repetitive process typically requiring laborious efforts. In an effort to alleviate such a burden, we have developed a set of evolving automation tools, known as xGTWay, as part of our research and development projects. Over the last 7 years, xGTWay has evolved through numerous evolutions yet maintaining the same objectives as its predecessor (i.e.to automate unit testing as much as possible). In this paper, the entire generations of xGTWay are presented along with the comparative analysis between them.